Eating habits, physical activity, nutrition knowledge, and self-efficacy by obesity status in upper-grade elementary school students - Ha, Seong Ah (Nutr Res Pract, 2016)
BACKGROUND/OBJECTIVES: Childhood obesity has increased in recent decades in Korea. This study was designed to examine differences in the eating habits, physical activity (PA), nutrition knowledge, and self-efficacy of children by obesity status. SUBJECTS/METHODS: Subjects were 5th-grade children from 70 elementary schools in 17 cities nationwide. Two-stage stratified cluster sampling was employed. Survey questionnaire included items related to general characteristics, eating habits, PA, nutrition knowledge and self-efficacy. Excluding incomplete responses, 3,531 data were analyzed using SPSS. Subjects were categorized into overweight·obesity (OW) and normal weight (NW) groups based on body mass index percentiles for age by sex. RESULTS: A total of 21.5% of subjects was overweight or obese. There were significant differences in gender, perceived stress, perception of body shape, body satisfaction, and interest in weight control between the OW and NW groups (P < 0.001). With respect to eating habits, the OW group ate breakfast (P < 0.05) and snacks (P < 0.01) less frequently, ate bigger meals (P < 0.001), and demonstrated less desirable behaviors during meals (P <0.05 in boys) compared to the NW group. The OW group participated in less PA than the NW group, especially boys. OW boys spent less time walking during weekdays (P < 0.05) or the weekend (P < 0.001), spent more time being sedentary during weekdays or the weekend (P < 0.001), and exercised a fewer number of days (P < 0.01). For girls, the OW group spent more time being sedentary during the weekend (P < 0.01) and exercised a fewer number of days by walking or bicycle riding (P < 0.05) than the NW group. Nutrition knowledge was not significantly different between the OW and NW groups. Self-efficacy (P < 0.01 in boys), especially PA self-efficacy (P < 0.01), was significantly lower in the OW than NW group. CONCLUSIONS: This study revealed differences in eating habits, PA, and self-efficacy between OW and NW children. Obesity management programs for children need to focus on increasing self-efficacy, modifying eating habits, and increasing PA.